Developing IoT-Based Smart Audio System Using SDLC Approach - Nur Azmi Ainul Bashir; Restiadi Bayu Taruno; Istiqomah, Sintia Khorin Arafah; Saputri, Chumaidah Dwi Yoga (International Journal of Informatics and Computation, 2026)
Educational institutions have increasingly adopted digital technologies to automate learning support facilities. This study develops an IoT-based Smart Audio System to support the smart pesantren concept using an adapted System Development Life Cycle (SDLC) approach. The research aims to transform a conventional manually operated audio system into an integrated, automated, and priority-based system capable of managing primary schedules, adhan, and announcements within a unified architecture. The development process follows structured stages of planning, analysis, implementation, integration, and testing to ensure systematic requirement traceability, logical stability, and controlled hardware–software integration. A rule-based priority mechanism is implemented to guarantee deterministic handling of scheduling conflicts, with adhan assigned the highest priority, followed by announcements and primary audio playback. Laboratory-scale validation demonstrates a 100% functional success rate across 10 repeated test scenarios for each core module, confirming system consistency and reliability. IoT-based remote control testing records an average response time of 1.63 seconds, indicating responsive and stable performance for operational needs. Compared to the previous manual system, which is prone to human error and execution delays, the proposed system significantly improves timing accuracy, priority logic stability, and management efficiency. These findings confirm that the structured application of SDLC effectively enhances the quality and reliability of integrated IoT-based systems while contributing to the digital transformation of audio management in Islamic boarding school environments.